Both High and Low HbA1c Predict Incident Heart Failure in Type 2 Diabetes Mellitus. (March 2015) - Parry, Helen M.; Deshmukh, Harshal; Levin, Daniel; Van Zuydam, Natalie; Elder, Douglas H.J.; Morris, Andrew D.; Struthers, Allan D.; Palmer, Colin N.A.; Doney, Alex S.F.; Lang, Chim C.
Abstract : Background—: Type 2 diabetes mellitus is an independent risk factor for heart failure development, but the relationship between incident heart failure and antecedent glycemia has not been evaluated. Methods and Results—: The Genetics of Diabetes Audit and Research in Tayside Study study holds data for 8683 individuals with type 2 diabetes mellitus. Dispensed prescribing, hospital admission data, and echocardiography reports were linked to extract incident heart failure cases from December 1998 to August 2011. All available HbA1c measures until heart failure development or end of study were used to model HbA1c time-dependently. Individuals were observed from study enrolment until heart failure development or end of study. Proportional hazard regression calculated heart failure development risk associated with specific HbA1c ranges accounting for comorbidities associated with heart failure, including blood pressure, body mass index, and coronary artery disease. Seven hundred and one individuals with type 2 diabetes mellitus (8%) developed heart failure during follow up (mean 5.5 years, ±2.8 years). Time-updated analysis with longitudinal HbA1c showed that both HbA1c <6% (hazard ratio =1.60; 95% confidence interval, 1.38–1.86; P value <0.0001) and HbA1c >10% (hazard ratio =1.80; 95% confidence interval, 1.60–2.16; P value <0.0001) were independently associated with the risk of heart failure. Conclusions—: Both high and low HbA1c predicted heart failure development in our cohort, forming a U-shaped relationship.